Arctic expedition, 1875-6 : journals and proceedings of the Arctic expedition under the command of Captain Sir George S. Nares. (London : Harrison & Sons, 1877)
Expedition of 1875-76 by "Alert" and "Discovery" under the command of Captain Nares. Mode of access: Internet.